2023
DOI: 10.3390/ijerph20043305
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal and Head and Neck Cancer Patients Attending Ocean Road Cancer Institute in Tanzania from 2019 to 2021: An Observational Study

Abstract: Background: Cancer in Africa is an emerging public health problem that needs urgent preventive measures, particularly in workplaces where exposure to carcinogens may occur. In Tanzania, the incidence rate of cancer and mortality rates due to cancers are increasing, with approximately 50,000 new cases each year. This is estimated to double by 2030. Methods: Our hospital-based cross-sectional study describes the characteristics of newly diagnosed patients with head and neck or esophageal cancer from the Ocean Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…15 - 17 Recent evidence from a tertiary cancer-specialized hospital also indicated that 25% of patients with esophageal, head and neck cancers were tobacco users. 18 Further evidence from the 2018 Global Adult Tobacco Survey (GATS) revealed that overall tobacco use (including smoking and/or smokeless forms) among adults aged 15 years and above was 8.7%. Males accounted for 14.6% of users, while females represented 3.2%, resulting in approximately 17,200 tobacco-associated deaths annually.…”
Section: Introductionmentioning
confidence: 99%
“…15 - 17 Recent evidence from a tertiary cancer-specialized hospital also indicated that 25% of patients with esophageal, head and neck cancers were tobacco users. 18 Further evidence from the 2018 Global Adult Tobacco Survey (GATS) revealed that overall tobacco use (including smoking and/or smokeless forms) among adults aged 15 years and above was 8.7%. Males accounted for 14.6% of users, while females represented 3.2%, resulting in approximately 17,200 tobacco-associated deaths annually.…”
Section: Introductionmentioning
confidence: 99%